THE EFFECT OF ABA ENGLISH APPLICATION ON THE STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE OF MTs SWASTA AL KHOIR MANANTI PADANG LAWAS - Marjannah Nasution, Siti (BRIGHT VISION Journal of Language and Education, 2024)
The aim of this study is to answer the following questions: when they taught with the ABA English Application without the ABA English Application, the students' report cards in vocabulary mastery are better. The subjects in this study were 25 students of Class VIII-B MTs Swasta Al-Khoir Mananti Padang Lawas. The results revealed that: ABA English Application shows that in test implementation, particularly in vocabulary mastery, the use of applications in learning can produce good scores. It can be seen from the grades of the students. The assessment of test outcomes focuses on the learners' vocabulary mastery of the students. The assessment of test results is focused on students’ vocabulary mastery in the learners. The normality and homogeneity test was used for the interpretation of the requirements test, while the t-test formula was used for data analysis.The authors continued after the data was analyzed; (1) The learning outcomes of students’ understanding of new vocabulary using the ABA English application reached 80.24 and a standard deviation of 7.102. (2) The learning outcomes of students' understanding of new vocabulary obtained did not use the 68.4 application and the standard deviation of 6,244 t test values were 167.72 and ttable 1.708. So, the ttest is higher than the ttable. So that, the alternative hypothesis (Ha) proposed is accepted and zero (Ho) is rejected. This means that both the use of the ABA English Application for student achievement in  mastering new vocabulary based  on  the results  of  this  study,  the suggestion is that the ABA English application can be used as an alternative medium in learning to vocabulary mastery.